2022
DOI: 10.3389/fnins.2022.755393
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Movements During Navigation in a Virtual Environment: Sex Differences and Relationship to Sex Hormones

Abstract: Sex differences in spatial navigation have been related to different navigation strategies. For example, women are more likely to utilize local landmark-information in the environment compared to men. Furthermore, sex differences appear to be more pronounced when distances need to be judged in Euclidian terms and an allocentric representation of the environment is necessary. This suggests differential attentional processes during spatial navigation in men and women. However, eye-tracking studies on spatial nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
1
1
0
1
Order By: Relevance
“…Females are more susceptible to motion sickness than males in the other percentile but less susceptible than males in the first percentile. This finding is consistent with most research [35]- [40]. Females may also be more susceptible to motion sickness because of their smaller body stature, which includes a smaller body shape and smaller feet, thus reducing their sense of stability [41].…”
Section: Percentile Differentiation Between Gendersupporting
confidence: 90%
“…Females are more susceptible to motion sickness than males in the other percentile but less susceptible than males in the first percentile. This finding is consistent with most research [35]- [40]. Females may also be more susceptible to motion sickness because of their smaller body stature, which includes a smaller body shape and smaller feet, thus reducing their sense of stability [41].…”
Section: Percentile Differentiation Between Gendersupporting
confidence: 90%
“…В случае, если наблюдается большое количество фиксаций внутри одного стимула (региона интереса), возможно, наблюдается склонность к дробной (или аналитической) стратегии, при которой стимулы как бы разбиваются на отдельные фрагменты. Подобная логика анализа используется и в навигационных исследованиях, когда рассчитывается, например, количество фиксаций на деталях маршрута как индикатор маршрутной стратегии [90] и количество фиксаций на полу и стенах для оценки евклидовых расстояний для обзорной стратегии [91]. Ключевым ограничением предложенных метрик является то, что почти все они исходят из предварительно размеченных областей интереса, сфокусированных на конкретных стимулах, соответственно, эти метрики плохо генерализуются между тестами.…”
Section: результаты айтрекинговых исследованийunclassified
“…The strong argument in favor of the ET to be used in education is that previous research has shown that eye movements are linked with different psychological characteristics, such as verbal and spatial abilities, as well as reasoning ability and working memory . For example, several recent studies have shown that (1) participants utilize various strategies (e.g., holistic–performing manipulations with the whole object, vs piecemeal–dividing it into pieces and manipulating them separately) to solve a spatial task, including in chemistry; (2) these strategies could be assessed with eye-tracking using fixations and saccades; (3) ET might bring some novel knowledge that is impossible to obtain with traditional methods, e.g., showing that strategies are flexible and are changed with increase in complexity of task. Given that, it is possible to use ET for identification of cognitive differences between students that can be used to adjust the educational program to a particular student. Eye-tracking has already been successfully implemented into the assessment of participant’s characteristics without tedious psychological testing (e.g., using long personality questionnaires) in several studies.…”
Section: Introductionmentioning
confidence: 99%